Propuesta de Creación e Implementación de una Oficina de Gestión de Proyectos en el Instituto Costarricense de Acueductos y Alcantarillados (AyA). - Hernández-Ramírez, Fabio (Instituto Tecnológico de Costa Rica, 2015)
The AyA is the governing body of water supply and sanitation in Costa Rica. As such, this institution must execute projects that contribute to the welfare and health of the Costa Rican population in an efficient, effective and sustainable manner. However, the application of best practices in project management is not part of the reality of this institution, which seriously affects the efficiency in the execution of its projects, measured on the basis of percentages of execution of the budget allocated. In this research, a compilation of information available in the institution and other external sources, as well as a diagnostic level of maturity in project management was performed, whereby was obtained a maturity level of 19.0%, broken performed by 26.7% at project level, 17.3% at the program level and 12.8% at the level of portfolios. Based on the diagnosis made, and other inputs such as bibliographic sources, institutional manuals and interviews; the design of a Project Management Office at the institution was executed. This design includes the necessary personnel, roles and responsibilities, implementation phases, its location within the organizational structure and management of internal and external communication. Through the implementation of this Office, is proposed as a goal to achieve an increase in the maturity level from a 19% today to 85% in 8 years, through a process of acculturation in project management, which should have the organizational support of the Institucional CEO. Key words: AyA, government project management office, project management maturity models.
Proyecto de graduación (Maestría en Gerencia de Proyectos). Instituto Tecnológico de Costa rica. Área Académica de Gerencia de Proyectos, 2015.
Keywords: Organizaciones gubernamentales; Modelos de madurez; Gestión de proyectos; Prácticas; Gerencia